2020
DOI: 10.3906/vet-1810-41
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milk urea level on fertility parameters in Holstein–Friesian dairy cows

Abstract: The objective of this study was to reveal the effect of milk urea levels on the fertility of dairy cows, taking into account their age, herd production level, number of cows, season of first insemination, which were analyzed using data from the SYMLEK national system. The study included data on milk urea levels in 88,745 test-day yields of 55,685 Holstein-Friesian cows, which were milked up to 30 days before first insemination, during the period preceding 180 days of first and second lactation. The GLM procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In addition, to reduce potential unfavorable correlated responses, correlations of MU and traits included in the breeding goal have to be considered. Previous research showed that MU (or MUN) is correlated with yield traits (e.g., milk, protein, and fat yields; Yin et al, 2012;Beatson et al, 2019;Ariyarathne et al, 2021), type traits (Satoła et al, 2017b), BW (Hojman et al, 2005), SCC (Bobbo et al, 2019), and reproductive performance (Siatka et al, 2020;Kananub et al, 2020). However, results were not all indicating similar direction and strength of correlations.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, to reduce potential unfavorable correlated responses, correlations of MU and traits included in the breeding goal have to be considered. Previous research showed that MU (or MUN) is correlated with yield traits (e.g., milk, protein, and fat yields; Yin et al, 2012;Beatson et al, 2019;Ariyarathne et al, 2021), type traits (Satoła et al, 2017b), BW (Hojman et al, 2005), SCC (Bobbo et al, 2019), and reproductive performance (Siatka et al, 2020;Kananub et al, 2020). However, results were not all indicating similar direction and strength of correlations.…”
Section: Introductionmentioning
confidence: 92%
“…The slightly positive genetic relationship found between MU and FF may be due to the slightly negative correlation between MU and MY and the relatively strong expectation that there is a negative correlation between FF and MY. Siatka et al (2020) reported that MU had a significant negative effect on the fertility of high-yielding dairy cattle. Moreover, the approximate genetic correlation found between MU and FF was lower at the end of the lactation (325 DIM).…”
Section: Approximate Genetic Correlations With Other Traits Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen emissions from livestock can have harmful effects on biodiversity, soil, water and air quality, as they account for 23% of global nitrous oxide and 60% of global ammonia (NH 3 ) emissions 4 . Besides, an increase in MUC from 150 to 300 mg/L reduces fertility, and levels above 300 mg/L are associated with infertility of cows 5,6 . Therefore, minimizing MUC without compromising the nutritional requirements of the animals may reduce environmental burden and increase fertility.It has been shown that MUC is a moderately heritable trait 7,8 and proposed that selection of cows for lower MUC concentration would reduce urinary urea and N emissions and thus the environmental footprint 1 .…”
mentioning
confidence: 99%
“…Nitrogen emissions from livestock can have harmful effects on biodiversity, soil, water and air quality, as they account for 23% of global nitrous oxide and 60% of global ammonia (NH 3 ) emissions 3 . Besides, increased MUC is directly associated with infertility of cows 4,5 . Therefore, minimizing MUC without compromising the nutritional requirements of the animals may reduce environmental burden and increase fertility.…”
Section: Introductionmentioning
confidence: 99%